White Fang - London, Jack, 1876-1916.; Viney, Brigit (Harlow, Essex : Pearson Education, 2008)
Follows the adventures of a dog who is part wolf as he eventually makes his peace with man in the wilderness of northern Canada.
5.5
5-8
7-9
Keywords: Dogs -- Fiction; Wolves -- Fiction; Dogs -- Fiction; Wolves -- Fiction; Canada -- Fiction; Canada -- Fiction